Comparison of the toxicokinetics of daidzein and bisphenol A in pregnant and non-pregnant DA/Han rats - Silvia Selinski; Gisela H. Degen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
Potentially adverse human and environmental effects due to hormone mimicry of environmental estrogens are a matter of current concern. Environmental estrogens belong to the socalled endocrine active compounds (EAC) and may alter signalling processes of the endocrine system leading to a broad range of effects during fetal and postnatal development, puberty, adulthood, and aging. A number of synthetic chemicals as well as several plant-derived compounds, socalled phytoestrogens, are known to have weak estrogenic activity. The present study is part of the risk assessment of the weak environmental estrogens daidzein and bisphenol A. The isoflavone daidzein is an important phytoestrogen with respect to dietary exposure (soy beans and soy products) whereas bisphenol A is an industrial chemical that occurs at much lower concentrations as a contaminant in food. The toxicokinetics of these compounds in female pregnant and non-pregnant DA/Han rats after single intravenous application were compared by the use of the Mann-Whitney- U-statistic.
Keywords: 519; Bisphenol A; daidzein; xenoestrogens; phytoestrogens; endocrine active compounds; Mann-Whitney-U-test; Theorie